HUBUNGAN BUDAYA KESELAMATAN DAN PERILAKU BERKENDARA AMAN PENGEMUDI DI JALAN TOL PEKANBARU DUMAI - Triani Wulandari; Zulfan Saam; Ridwan Manda Putra (Program Pascasarjana Universitas Riau, 2022)
The role of transportation for the community has a tremendous impact, especially in daily life activities. In transportation sector, especially land transportation, toll road has a major role in determining the pace of the economy and the level of community prosperity. The condition of the toll road with the facilities available on it capable of supporting the movement of vehicles with a high average speed and in a fast travel time can be considered as an adjustment solution to increase mobility, but in fact these conditions lead to potential traffic accidents. Implementation of safety driving related to the phenomenon of traffic accidents which are the main concern or problem on toll road by creating a decent safety culture. Safety culture is a tendency of attitudes, beliefs, and perceptions that naturally spread within groups that are embodied in rules and values, which are seen in how they act in relation to risk and control systems. This study aims to determine the relationship between safety culture and safety driving among drivers of Pekanbaru Dumai toll road. The subject of this study found 60 drivers who use the Pekanbaru Dumai toll road. Researchers used a safety culture and safety driving questionnaire.The results of this study indicate a very significant positive relationship between safety culture and safety driving, with r = 0.732, p <0.01, r2 = 0.536. It can be concluded that safety culture is one of the factors safety driving among drivers Pekanbaru Dumai toll road with percentage of effect 53.6%, although only one dimension is significant with safety driving.